2005
DOI: 10.1159/000087488
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transtentorial Ventriculocystostomy and Cystoventriculoperitoneal Shunt in a Neonate with Dandy-Walker Malformation and Associated Aqueductal Obstruction

Abstract: Objective: Shunting of the lateral ventricle and the posterior fossa cyst is the advocated surgical therapy for children with Dandy-Walker malformation (DWM) and associated aqueductal obstruction. The high rate of complications of combined shunting stimulated the authors to search for an alternative surgical solution. Clinical Presentation/Intervention: After transtentorial endoscopic ventriculocystostomy, a cystoventricular catheter, connected to a peritoneal shunt, was placed in a neonate with DWM and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…However, Asai et al [15] reported that C-P shunt plus V-P shunt surgery may lead to secondary aquaductus cerebri stenosis. On the other hand, endoscopic surgery is also used in treatment of patients with D-WS [22,28,29,30]. Weinzierl et al [30] reported that cystoventriculoperitoneal shunt placement after transtentorial endoscopic ventriculostomy was a surgical alternative in a neonate with D-WS associated aqueductal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Asai et al [15] reported that C-P shunt plus V-P shunt surgery may lead to secondary aquaductus cerebri stenosis. On the other hand, endoscopic surgery is also used in treatment of patients with D-WS [22,28,29,30]. Weinzierl et al [30] reported that cystoventriculoperitoneal shunt placement after transtentorial endoscopic ventriculostomy was a surgical alternative in a neonate with D-WS associated aqueductal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, endoscopic surgery is also used in treatment of patients with D-WS [22,28,29,30]. Weinzierl et al [30] reported that cystoventriculoperitoneal shunt placement after transtentorial endoscopic ventriculostomy was a surgical alternative in a neonate with D-WS associated aqueductal obstruction. Sikorski and Curry [29] described an endoscopic technique for hydrocephalus related to D-WS.…”
Section: Discussionmentioning
confidence: 99%
“…19,22) This maneuver minimizes the complexity associated with the placement of combined VP and CP shunts, avoids CP shunt-associated complications, and facilitates transtentorial ventricular pressure equalization. However, sophisticated instrumentation and relatively complicated maneuvers are required.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management of this disorder has shifted from craniectomy and excision or fenestration of the cyst wall to the placement of various shunts. 1,5,9,[11][12][13][14]22) Lateral ventriculoperitoneal (VP), cyst-peritoneal (CP), and combined VP and CP shunts have been placed and endoscopic third ventriculostomy (ETV) has been performed in the past decade. 14) Transaqueductal placement of a multiperforated shunt catheter has been used to treat isolated fourth ventricle, 20,21) but not hydrocephalus associated with DWM.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the surgical procedures is not yet completed. Since the description of this entity by Dandy and Blackfan [7] and later by Taggart and Walker [8], various methods such as posterior fossa surgery with membrane excision, ventriculoperitoneal shunting (VPS), cystoperitoneal shunting (CPS) or combinations have been used [9,10]. …”
Section: Introductionmentioning
confidence: 99%